Peningkatan Kualitas Layanan Melalui Penguatan Kompetensi Profesional, Kepribadian, Dan Kepuasan Kerja menggunakan Metode Korelasional dan Analisis SITOREM - Abidin, Zaenal; Supriyatin; Ahmad Sofyan (Edusifa: Jurnal Pendidikan Islam, 2023)
The quality of teacher service is very important in educational organizations to achieve the stated goals. Early childhood education is very important, fundamental, and strategic in building human resources and preparing a qualified generation of the nation, so it must be implemented as well as possible. Kindergarten teachers must be well prepared in order to provide quality services. Based on the above background, this study aims to look at and find efforts and strategies that can be used to improve the quality of teacher services through strengthening professional competence, personality, and job satisfaction for Kindergarten teachers in Bogor City. This research uses correlational research method, the research is conducted using quantitative methods and data collection is carried out through a questionnaire. then explained by statistical analysis and analyzed by regression analysis. The study population was 298 private Kindergarten teachers with A accreditation in Bogor City. The research sample of 171 respondents was determined by the Slovin formula, selected using proportional random sampling method. The results of quantitative research found that professional competence that emphasizes the ability to develop teaching materials, learning approaches, and developing teaching materials can improve teacher quality. Personality that emphasizes awareness, friendliness, emotional stability, openness to experience, extraversion can improve the quality of teacher services. Job satisfaction that emphasizes salary, employment, promotion opportunities, supervisors, colleagues can improve the quality of teacher service. Based on this research, the stronger the professional service competence, personality, and job satisfaction, the higher the teacher quality. The results showed that there was a positive and significant relationship between professional competence and the quality of teacher services with the coefficient of determination r2y1 = 0.417. There is a positive and significant relationship between personality and service quality with the coefficient of determination r2y2 = 0.515. There is a positive and significant relationship between job satisfaction and service quality with the coefficient of determination r2y3 = 0.463. This shows that the quality of teacher services can be improved by increasing professional competence, personality, and job satisfaction. The results of the SITOREM analysis on professional competence, personality, job satisfaction and teacher service quality show that there are indicators that are priority to be improved, namely: emotional stability, agreeableness, extraversion, pay, job, promotion opportunities, supervisors, designing learning approaches, developing teaching materials, develop professionalism, responsiveness. The indicators that need to be maintained are: openness to experience, conscientiousness, co-workers, reliability, tangibles, assurance, and empathy. Keyword: professional competence, personality, job satisfaction, quality of service